Description of Bread Making Training Program Management for the Community in Jorong VI Parit Panjang Lubuk Basung District - Bella Puspita Sari; Vevi Sunarti (Universitas Negeri Padang, 2023)
The background to this research was due to the success of the bread making training which was marked by the success of mothers opening a cake business at the Nagari Lubuk Basung Vocational Training Center (BLK), this was allegedly due to the management of the implementation of the training program. The purpose of this study is to describe the management of the implementation of training programs in terms of planning, implementation, evaluation and implementation. This research is a quantitative descriptive type, with a population of people in Jorong VI Parit Panjang, Lubung Basung District. The sampling technique was Simple Random Sampling which was taken as many as 16 people. Data collection techniques using a questionnaire. While the data collection tool is a questionnaire. Data analysis techniques use the percentage formula. The results of the study showed that the implementation of Bread Making training for the community in Jorong VI Parit Panjang, Lubuk Basung Pertama District, from a planning perspective, was categorized as very supportive. Second, in terms of implementation, it is categorized as very supportive. Third, from the evaluation aspect it is categorized as supportive. Fourth, in terms of implementation it is categorized as supportive